Multi-Disciplinarity and Collaboration in Computational Design Teams - Kasalı, Altuğ; Altintas, Livanur Erbil; Doğan, Fehmi; Kasali, Altug; Dogan, Fehmi (Ecaade-Education & Research Computer Aided Architectural Design Europe, 2022)
This study reports cases involving computational practices in architectural design to understand how a distributed cognitive system supports multidisciplinary collaboration in design teams. In particular, we look into the role of coding languages in collaborative practices within interdisciplinary design teams. By providing an analysis on the distributed nature of the design process, this research aims to explain collaboration involving team participants with different skills in representation.
Erbil Altintas, Livanur/0000-0002-4134-0410
Keywords: Collaboration; Distributed Cognition; Computation; Multidisciplinary